Thrombospondin-1 is an endogenous activator of TGF-β in experimental diabetic nephropathy in vivo - Daniel, Christoph; Schaub, Kathrin; Amann, Kerstin Ute; Lawler, Jack; Hugo, Christian (Diabetes, 2007)
OBJECTIVE - Transforming growth factor-β (TGF-β), the central cytokine responsible for the development of diabetic nephropathy, is usually secreted as a latent procytokine complex that has to be activated before it can bind to its receptors. Recent studies by our group demonstrated that thrombospondin-1 (TSP-1) is the major activator of latent TGF-β in experimental glomerulonephritis in the rat, but its role in diabetic nephropathy in vivo is unknown. RESEARCH DESIGN AND METHODS - Type 1 diabetes was induced in wild-type (n = 27) and TSP-1-deficient mice (n = 36) via streptozotocin injection, and diabetic nephropathy was investigated after 7, 9.5, and 20 weeks. Renal histology, TGF-β activation, matrix accumulation, and inflammation were assessed by immunohistology. Expression of fibronectin and TGF-β was evaluated using real-time PCR. Furthermore, functional parameters were examined. RESULTS - In TSP-1-deficient compared with wild-type mice, the amount of active TGF-β within glomeruli was significantly lower, as indicated by staining with specific antibodies against active TGF-β or the TGF-β signaling molecule phospho-smad2/3 or the typical TGF-β target gene product plasminogen activator inhibitor-1. In contrast, the amount of glomerular total TGF-β remained unchanged. The development of diabetic nephropathy was attenuated in TSP-1-deficient mice as demonstrated by a significant reduction of glomerulosclerosis, glomerular matrix accumulation, podocyte injury, renal infiltration with inflammatory cells, and renal functional parameters. CONCLUSIONS - We conclude that TSP-1 is an important activator of TGF-β in diabetic nephropathy in vivo. TSP-1-blocking therapies may be considered a promising future treatment option for diabetic nephropathy. © 2007 by the American Diabetes Association.
Created from Fastlane, Scopus look-up